The effect of different dietary manipulations on haematological properties in Japanese quail - Reda, Gebrehaweria K.; Ndunguru, Sawadi F.; Csernus, Brigitta; Lugata, James K.; Knop, Renáta; Szabó, Csaba; Czeglédi, Levente (Acta Agraria Debreceniensis, 2024)
Quantitative and qualitative dietary conditions are crucial for physiological functions. Blood haematology, the indicator of immune regulation, is critically affected by dietary conditions. Despite their importance, the effect of macro- and micronutrient manipulation remains unknown. We used feed restriction, energy or protein restriction, and supplementation of leucine, methionine, or both on top of restricted-feeding to study the effect on haematological properties in Japanese quail. Fifty-six birds of six weeks of age were distributed into seven treatments; control, 20% feed restriction, 20% energy restriction, 20% protein restriction, supplementing 20% leucine, 20% methionine, or both on top of restricted feeding. Haematological properties, including white blood cell count, number and percent of lymphocytes, mid-range (eosinophil + basophil), granulocytes, red blood cell count, haemoglobin levels, packed cell volume, mean corpuscular volume, and mean corpuscular haemoglobin were analysed. We found that quantitative feed restriction, energy restriction, and amino acid supplementations showed no significant effect compared to the control group. However, protein restriction reduced all indices, suggesting the importance of proteins in maintaining leukocyte and erythrocyte indices. The present study revealed that neither moderate calorie restriction nor moderate specific amino acid supplementation have an impact on blood haematology, while 20% protein restriction has a notable effect.